Desain math e-learning berbasis moodle pada sekolah penggerak - Setyawan, Fajar Arif; Masduki, Lusi Rachmiazasi (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The Indonesian Ministry of Education launched a School Program which is named by “Program Sekolah Penggerak” with the hope of creating a generation of lifelong learners who have personalities as Pancasila Students. SMA Negeri 2 Ungaran is one of school that passed the selection as a “Sekolah Penggerak” in Semarang Regency. Therefore, learning and conducting assessments of student learning outcomes must be done holistically. To support the success of learning and assessment, especially in mathematics, a Moodle-based Math E-Learning design was developed using interviews, surveys and literature studies. The results obtained in the development of Math E-Learning is a Moodle-based Learning Management System (LMS) with menus that can facilitate teachers in providing materials and assessments according to the curriculum at SMA Negeri 2 Ungaran as school of “Sekolah Penggerak”.